Gradient and asymmetric copolymers: the role of the copolymer composition profile in the ionization of weak polyelectrolytes. Issue 47 (17th November 2020) - Farias-Mancilla, Barbara; Zhang, Junliang; Kulai, Ihor; Destarac, Mathias; Schubert, Ulrich S.; Guerrero-Sanchez, Carlos; Harrisson, Simon; Colombani, Olivier
Abstract : The ionization of weak polyelectrolytes can be altered by controlling the composition profile of the comonomers along the chain. Abstract : Weak (or annealed) polyelectrolytes are polymers containing weak acidic or basic units. The behavior of these polymers in aqueous medium depends on their ionization state, which in turn varies with the pH value. By studying copolymers of acrylic acid (AA) and n -butyl acrylate ( n BA) units as an example, we show that the relationship between pH value and degree of ionization of copolymers consisting of weak acidic units and hydrophobic units can be modified by controlling the composition profile along the copolymer chain at a constant content of acidic units. In particular, the ionization of a gradient copolymer, which exhibits a non homogeneous composition profile varying continuously along the copolymer chain, could be understood by studying model statistical and block copolymers exhibiting respectively a constant or a step-wise composition profile along the chain.